Convalescent plasma in the management of moderate covid-19 in adults in India: open label phase II multicentre randomised controlled trial (PLACID Trial). (22nd October 2020) - Agarwal, Anup; Mukherjee, Aparna; Kumar, Gunjan; Chatterjee, Pranab; Bhatnagar, Tarun; Malhotra, Pankaj
Abstract: Objective: To investigate the effectiveness of using convalescent plasma to treat moderate coronavirus disease 2019 (covid-19) in adults in India. Design: Open label, parallel arm, phase II, multicentre, randomised controlled trial. Setting: 39 public and private hospitals across India. Participants: 464 adults (≥18 years) admitted to hospital (screened 22 April to 14 July 2020) with confirmed moderate covid-19 (partial pressure of oxygen in arterial blood/fraction of inspired oxygen (PaO2 /FiO2 ) ratio between 200 mm Hg and 300 mm Hg or a respiratory rate of more than 24/min with oxygen saturation 93% or less on room air): 235 were assigned to convalescent plasma with best standard of care (intervention arm) and 229 to best standard of care only (control arm). Interventions: Participants in the intervention arm received two doses of 200 mL convalescent plasma, transfused 24 hours apart. The presence and levels of neutralising antibodies were not measured a priori; stored samples were assayed at the end of the study. Main outcome measure: Composite of progression to severe disease (PaO2 /FiO2 <100 mm Hg) or all cause mortality at 28 days post-enrolment. Results: Progression to severe disease or all cause mortality at 28 days after enrolment occurred in 44 (19%) participants in the intervention arm and 41 (18%) in the control arm (risk difference 0.008 (95% confidence interval −0.062 to 0.078); risk ratio 1.04, 95% confidence interval 0.71 to 1.54). Conclusion: Convalescent plasma was not associated with a reduction in progression to severe covid-19 or all cause mortality. This trial has high generalisability and approximates convalescent plasma use in real life settings with limited laboratory capacity. A priori measurement of neutralising antibody titres in donors and participants might further clarify the role of convalescent plasma in the management of covid-19. Trial registration: Clinical Trial Registry of India CTRI/2020/04/024775.